Analysis of the Adoption of Digital Marketing in MSMEs in the Era of the Covid-19 Pandemic - Prima Ayundyayasti; Sarana Sarana; Afiat Sadida; Sugiarti Sugiarti; Agus Suwondo (Pusat P2M Politeknik Negeri Batam, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the most numerous forms of business in Indonesia. This creates high competition among business actors. The conditions of Covid-19 pandemic are increasing the business competition with restriction on community activities including restriction towards business activites set by the government. Many business fields such as food, beverage, and creative industries are affected by this circumstance. MSME actors are trying to survive the business in the midst of a pandemic. Digital marketing is a form of marketing effort by MSMEs so that they can still operate their business. The role of digital marketing is not only to market produts, but also as a means of communicating with customers, disseminating information, and providing convenience for transactions. The purpose of this research is to analyze digital marketing adoption by MSMEs in the era of Covid-19 pandemin in Indonesia. The approach applied in this research is the Technology Organization Environment (TOE) model with quantitative research method. The total of 244 MSMEs are the respondents in this research. The results of this study show that the context of technology, organization and environment has a positive effect on digital marketing adoption by MSMEs in the era of the Covid-19 pandemic.